G-quadruplexes and helicases. Issue 5 (15th February 2016) - Mendoza, Oscar; Bourdoncle, Anne; Boulé, Jean-Baptiste; Brosh, Robert M.; Mergny, Jean-Louis
Abstract: Guanine-rich DNA strands can fold in vitro into non-canonical DNA structures called G-quadruplexes. These structures may be very stable under physiological conditions. Evidence suggests that G-quadruplex structures may act as 'knots' within genomic DNA, and it has been hypothesized that proteins may have evolved to remove these structures. The first indication of how G-quadruplex structures could be unfolded enzymatically came in the late 1990s with reports that some well-known duplex DNA helicases resolved these structures in vitro . Since then, the number of studies reporting G-quadruplex DNA unfolding by helicase enzymes has rapidly increased. The present review aims to present a general overview of the helicase/G-quadruplex field.